The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/00016340701709307
|View full text |Cite
|
Sign up to set email alerts
|

Stage I small cell carcinoma of the endometrium: survival and management options

Abstract: Small cell carcinoma (SCC) of the endometrium is a rare but aggressive disease with early systemic involvement. Patient survival is short. To date, no effective treatment protocol has been established. Surgery, radiotherapy, and chemotherapy have been used either alone or in combination. The case of a patient with stage IB endometrial SCC is presented with an overview based on all reported cases of SCC of the endometrium and its treatment with particular reference to stage I cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…There were no symptoms of paraneoplastic syndrome in the three cases presented here. Among the 80 cases of endometrial SCC that have been reported up to now, more than half of the patients with available data had stage III and IV disease (6). Two of the patients reported here had stage III and IV disease.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There were no symptoms of paraneoplastic syndrome in the three cases presented here. Among the 80 cases of endometrial SCC that have been reported up to now, more than half of the patients with available data had stage III and IV disease (6). Two of the patients reported here had stage III and IV disease.…”
Section: Discussionmentioning
confidence: 91%
“…The diagnosis of SCC of the endometrium needs evidence of endometrial origin, dense sheet-like growth of morphologically similar small tumour cells and immunohistochemical staining for at least one neuroendocrine marker (4). Some of the most common neuroendocrine markers that have been reported to be positive in these tumours are NSE, synaptophysin, chromogranin A and cytokeratin (1,5,6). In the first case, the tumour cells were strongly and diffusely positive for NSE, strongly and focally positive for pancytokeratin and LMWCK and negative for synaptophysin, chromogranin A and S100.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of primary small cell neuroendocrine carcinoma of the endometrium primarily relies upon immunohistochemical studies discerning neuroendocrine differentiation [8, 9]. Histopathologically, the disease is characterized by small tumor cells exhibiting sheet-like growth of endometrial origin [8].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, the disease is characterized by small tumor cells exhibiting sheet-like growth of endometrial origin [8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation